Functional and Radiological Outcome of Short Same Segment Instrumentation in Thoracolumbar Burst fracture - Thapa, Bishnu Babu; Shah, Rajesh Pratap (Journal of Nepal Health Research Council, 2023)
Background: Thoracolumbar region is important biomechanics transition zone in which rigid thoracic and flexible lumbar spine meet. This area is highly vulnerable to traumatic spinal fracture.Among all spine fracture, compression type is most common and managed conservatively. Thoracolumbar spine fracture can be associated with neurological deficit, spinal instability. The optimal treatment for these injuries is still controversy and subject for research.Methods: This retrospective study included 30 patients with single level thoracolumbar fracture.All the patients clinical and radiological parameters were evaluated preoperative, post-operative and 1 year follow up. Clinical parameters were included Visual analogue score, Oswestry disability index. Radiologic measurement were regional kyphotic angle by cobb’s method and anterior vertebral body height loss (Mumford’ santerior body compression equation method) in X-ray. All the data were analysed in SPSS version 20.Results: A total of 30 patients were included in this study,19 were male.The mean age of the patients were 40.8±13.The main cause of injury was fall from height,26 patients. The most common level of fracture vertebra was L1,11 patients.The mean difference of preop and postop kyphosis was 11.70±50 with P<0.05.The mean difference of preop Oswestry disability index and postop Oswestry disability index score was 30.7±7.6 with T score 22(P<0.05).The preop and postop Visual analogue score score also improved ,mean difference was 2.8±1(P<0.05).Conclusions: Short segment instrumentation with placement of pedicle screw at fracture vertebra is one option in the treatment of thoracolumbar burst fracture.Keywords: Burst; instability; kyphosis; neurological; thoracolumbar